THE ROLE OF LEADERSHIP IN ADVANCING INNOVATION IN FOOD AND NUTRITIONAL SCIENCES (International Journal of Food and Nutritional Sciences, 2021)
Leadership plays a pivotal role in advancing innovation within the field of food and nutritional sciences. This paper explores the various dimensions through which effective leadership drives progress, from fostering a culture of innovation to securing resources and facilitating interdisciplinary collaborations. By analysing case studies of successful leaders in the field, the study highlights strategies for promoting innovative practices, overcoming barriers, and achieving impactful advancements. The paper also discusses the implications of leadership on policy-making, research priorities, and the integration of cutting-edge technologies in food and nutrition. Ultimately, it underscores the importance of visionary leadership in addressing contemporary challenges and shaping the future of food and nutritional sciences.